The effect of a 24-week training focused on activities of daily living, muscle strengthening, and stability in idiopathic inflammatory myopathies: a monocentric controlled study with follow-up - Špiritović, Maja; Heřmánková, Barbora; Oreská, Sabína; Štorkánová, Hana; Růžičková, Olga; Vernerová, Lucia; Klein, Martin; Kubínová, Kateřina; Šmucrová, Hana; Rathouská, Adéla; Česák, Petr; Komarc, Martin; et al. (Arthritis research & therapy, 2021)
BACKGROUND: The structural and functional changes of the skeletal muscles in idiopathic inflammatory myopathies (IIM) caused by inflammation and immune changes can be severely disabling. The objective of this study was to assess the effect of a 24-week program combining a supervised training of activities of daily living (ADL), resistance, and stability with home exercise for improving muscle function, compared to a daily home-based exercise representing the regular outpatient care. METHODS: Fifty-seven patients with IIM were consecutively and non-selectively enrolled in an intervention (IG, n = 30) or control (CG, n = 27) group. Both groups were provided a standard-of-care pharmacological treatment and follow-up. Only the IG underwent the supervised intervention twice a week for 1 h per session. At baseline, 12, 24, and 48 weeks, all patients were assessed by an assessor blinded to the intervention for primary outcomes: muscle strength (Manual Muscle Testing of eight muscle groups [MMT-8]) and endurance (Functional Index-2 [FI-2]), and secondary outcomes: stability and body composition. Secondary outcomes also included questionnaires evaluating disability (Health Assessment Questionnaire [HAQ]), quality of life (Short Form 36 [SF-36]), depression (Beck's Depression Inventory-II [BDI-II]), and fatigue (Fatigue Impact Scale [FIS]), and analysis of the systemic and local inflammatory response and perceived exertion to assess the safety of the intervention. RESULTS: Twenty-seven patients in the IG and 23 in the CG completed the entire program and follow-up. At week 24, compared to deterioration in the CG, we found a significant improvement in the IG in muscle strength (mean % improvement compared to baseline by 26%), endurance (135%), disability (39%), depression (26%), stability (11%), and basal metabolism (2%) and a stabilization of fitness for physical exercise. The improvement was clinically meaningful (a 24-week change by >20%) in most outcomes in a substantial proportion of patients. Although the improvement was still present at 48 weeks, the effect was not sustained during follow-up. No significant increase in the systemic or local expression of inflammatory markers was found throughout the intervention. CONCLUSIONS: This 24-week supervised intervention focused on ADL training proved to be safe and effective. It not only prevented the progressive deterioration, but also resulted in a significant improvement in muscle strength, endurance, stability, and disability, which was clinically meaningful in a substantial proportion of patients. TRIAL REGISTRATION: ISRCTN35925199 (retrospectively registered on 22 May 2020).
Keywords: Activities of daily living; kosterní svaly; svalová síla; kvalita života; Stability; lidé; Activities of Daily Living; Endurance; Exercise Therapy; Muscle, Skeletal; následné studie; myozitida; Muscle Strength; Resistance training; Strength; činnosti denního života; Follow-Up Studies; Myositis; terapie cvičením; Quality of Life; Humans